The Role of Leadership in Improving Performance Through Organization Commitment, Motivation and Job Satisfaction of Village Employees - Pahlawi, Lukman Ahmad Imron; Fatonah, Siti (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to analyze the role of leadership in improving performance through organizational commitment, motivation, and job satisfaction of village employees. This research is survey research. This study used primary data. The sample in this study was 100 villages. The sampling technique is using the census method. The data was obtained from the results of the distribution of questionnaires. The analytical tool in this study is regression. The results showed that there is a significant leadership relationship against organizational commitment, motivation, and job satisfaction. Leadership, organizational commitment, motivation, and job satisfaction were substantial to performance. The total R2 of 0.989 indicates the Performance Assessment from the variables of Leadership, Organizational Commitment, Motivation, and Job Satisfaction is 98.9%. Job satisfaction is the most effective variable in improving performance because it has the most significant importance.